Pathology of Malignant Mesothelioma - Galateau-Sallé, Francoise.; Galateau-Sallé, Francoise. (Springer London : Imprint: Springer, 2006)
Mesothelioma is a global problem. Its incidence is rising in Europe, and it is a major health problem in the USA and other parts of the world, largely related to the previous use of asbestos products. Diagnosis, which rests on the pathology, is very difficult because of its diverse appearances and the potential for other diseases to mimic it. This monograph has been assembled by an international group of experts with a wealth of experience from France, UK, USA, Australia and Canada to aid in pathological diagnosis. In all these countries, the disease poses significant health problems. This book deals with clinical, radiological, epidemiological, molecular, and histopathological aspects of the disease. Tumors of the pleural, pericardial, peritoneal cavities as well as the ovary and tunica vaginalis are discussed. Differential diagnoses of serosal-based lesions are fully discussed and the use of immunohistochemical stains is explained. Plentiful illustrations give further aid to diagnosis This book is an essential reading for all diagnostic pathologists as well as general pathologists, who are sometimes required to diagnose the disease at biopsy or post mortem. It will be also invaluable read for members of the medical and legal professions who are involved with various aspects of this disease.